Нові результати прямого радіовуглецевого AMS датування кераміки буго-дністровської субнеолітичної культури - Гаскевич, Д.Л.; Ендо, Е.; Кунікіта, Д.; Яневич, О.О. (Археологія і давня історія України, 2020)
Публікуються та аналізуються 11 нових AMS
дат, одержаних в лабораторії Токійського університету за органічними включеннями в керамічному тісті та обвугленими залишками на поверхні
посудин з трьох пам’яток буго-дністровської культури. Крім двох аномально давніх дат, зроблених
за зразками з дуже низьким вмістом вуглецю, вони
потрапляють у діапазон 60—46 ст. до н. е. Traditional ideas about the origin of the Buh-Dnister
Culture (BDC) and its synchronisation with the Neolithic
cultures of the Danube-Carpathian region were
questioned by series of radiocarbon dates measured
on bones at the Kyiv laboratory in the 1998—2004. To
start addressing this problem, 11 AMS dates on orga-
nic inclusions in the ceramic paste and charred residues
on the surface of vessels were obtained at the Tokyo
University laboratory.
The set of new dates has given a wide scatter of their
values within the entire period outlined by the previous
BDC dates. Moreover, the two results of the second
quarter of the 7th millennium BC for the Hlynske 1 and
Bazkiv Ostriv site are beyond it and may potentially be
the oldest dates of the culture. However, analysis of the
samples in terms of carbon content, their susceptibility
to the influence of the freshwater reservoir effect, correspondence
to the stratigraphy of the sites and typology
of materials detected only six more credible dates.
Their order on the timeline coincides with generally
accepted ideas about the sequence of existence of the
different BDC pottery types. The youngest is the vessel
of the Savran type from Shumyliv-Cherniatka has yielded
two dates falling into the range of 4723—4491 cal
BC, when the Trypillia culture bearers already populat
the region. Two vessels of the Samchyntsi type from
Bazkiv Ostriv yield three dates within the range of
5288—4847 cal BC, which corresponds to their finding
next to fragments of fine «music-note» bowls of the Linear
Band Pottery Culture. The Skybyntsi type vessel
from Bazkiv Ostriv yield the oldest plausible date of
5621—5514 cal BC, which corresponds to the age of the
Criş monuments in Moldova.
Unfortunately, the new dates did not shed light on
the issues of the time and direction of the first pottery
spreading in the region. Thus, this needs further research
including reliably direct radiocarbon dating on
pottery.